Functional characterization of conserved small open reading frames on the genomic RNA of sonchus yellow net virus - Mengxin Gao; Shuang Ni; Yaqin Wang; Zhenghe Li; Pan Gong; Xueping Zhou; Fangfang Li (Phytopathology Research)
Abstract Sonchus yellow net virus (SYNV), a negative-sense single-stranded RNA (-ssRNA) virus belonging to the Rhabdoviridae family, encodes six known proteins, including five canonic structural proteins and the nonstructural movement protein Sc4. Using the ORF prediction software ViralORFfinder, we found that SYNV genomic RNA (gRNA) might contain small putative open reading frames (sORFs). However, the functions of these additional sORFs remain largely unexplored. In this study, we identified three conserved sORFs, termed A, B, and C on the gRNA of SYNV. The proteins encoded by these sORFs were found to localize to both the nucleus and cytoplasm. Subcellular localization combined with western blotting revealed a time-dependent decrease in the accumulation of these proteins. Bimolecular fluorescence complementation and co-immunoprecipitation assays confirmed the interactions between A and matrix protein (M), A and phosphoprotein (P), and B and P of SYNV. Mutation of the start codon of B (from AUG to AUA) to block its translation delayed the onset of viral infection, resulting in reduced pathogenicity with milder symptoms and less accumulation of viral RNAs in the late infection stage than the wild-type virus. Ectopic overexpression of A and B via the potato virus X (PVX)-based recombinant vector demonstrated that A and B enhanced PVX-CP accumulation and aggravated mosaic symptoms. These findings reveal the potential coding ability of the gRNA of SYNV and suggest that the identified sORFs may play a significant role in modulating viral pathogenicity. This study also highlights the importance of identifying additional coding capacity in viral genomes, which could provide new insights into the biology of -ssRNA viruses and lead to more opportunities for developing targeted antiviral strategies.